1997
DOI: 10.1159/000108415
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Concerning the Morphology and the Risk of Carotid Plaques

Abstract: An international consensus meeting to determine criteria for the characterization of extracranial carotid artery stenosis was held in Paris on December 13–14, 1996. Recommendations are the following if the degree of the stenosis and the precise location of the stenosis are well defined. Ultrasonic Doppler duplex methods describe the composition and the surface topography of carotid plaques. Echogenicity (from anechoic to hyperechoic), surface (from smooth to cavitated) and texture (from homogeneous to heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
10

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(90 citation statements)
references
References 21 publications
2
78
0
10
Order By: Relevance
“…In brief, the following ultrasound color-Doppler characteristics were examined: echogenicity of the lesion with respect to the vessel wall; presence of acoustic shadows inside the lesion; homogeneity of the lesion wall; profile of the endoluminal surface; and the presence or absence of a cleavage plain. Characterization of lesions was consistent with methods describing echogenicity and plaque surface appearance previously established by an International Consensus Conference concerning plaque morphology and risk (19).…”
Section: Methodssupporting
confidence: 67%
“…In brief, the following ultrasound color-Doppler characteristics were examined: echogenicity of the lesion with respect to the vessel wall; presence of acoustic shadows inside the lesion; homogeneity of the lesion wall; profile of the endoluminal surface; and the presence or absence of a cleavage plain. Characterization of lesions was consistent with methods describing echogenicity and plaque surface appearance previously established by an International Consensus Conference concerning plaque morphology and risk (19).…”
Section: Methodssupporting
confidence: 67%
“…44 For plaque morphology assessment, we used the Gray-Weale classification, 17 which is slightly different from the classification recommended in this consensus (4 grades instead of 5). We have paid particular attention to standardize echogenicity classification against defined and wellrecognized reference structures located adjacent to the …”
Section: Discussionmentioning
confidence: 99%
“…23 Ultrasonography is usually a technologist-dependent study, with variation also occurring from machine to machine. DeBray et al 24 suggested that echo-density measurement should be used to reflect the overall brightness of the plaque, with the term hyperechoic referring to echogenic plaque and the term hypoechoic referring to echolucent plaque. The terms homogeneous and heterogeneous should be used for plaque of uniform and nonuniform consistency, respectively, thus, expressing their ultrasonic texture.…”
Section: Aburahma Et Al Plaque Heterogeneity and Selection For Ceamentioning
confidence: 99%